2015
DOI: 10.1016/j.amepre.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of U.S.-Based Research on the Behavioral Risk Factor Surveillance System

Abstract: Background Since Alan Pritchard defined bibliometrics as “the application of statistical methods to media of communication” in 1969, bibliometric analyses have become widespread. To date, however, bibliometrics has not been used to analyze publications related to the U.S. Behavioral Risk Factor Surveillance System (BRFSS). Purpose To determine the most frequently cited BRFSS-related topical areas, institutions, and journals. Methods A search of the Web of Knowledge database in 2013 identified U.S.-publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 7 publications
0
77
0
4
Order By: Relevance
“…Yet, it lacks the comprehension of author keywords in terms of an article's content (Zhang et al, 2016). The application VOS viewer displays a plot a relevance distance-based map along with keyword relevance clusters derived from the reference sections (Khalil & Crawford, 2015). From information from Figure 4, it can be observed that the topmost frequent data extracted from the total references conducted between the years of 1990 to 2018 by KeyWords plus illustration.…”
Section: Keyword Plusmentioning
confidence: 99%
“…Yet, it lacks the comprehension of author keywords in terms of an article's content (Zhang et al, 2016). The application VOS viewer displays a plot a relevance distance-based map along with keyword relevance clusters derived from the reference sections (Khalil & Crawford, 2015). From information from Figure 4, it can be observed that the topmost frequent data extracted from the total references conducted between the years of 1990 to 2018 by KeyWords plus illustration.…”
Section: Keyword Plusmentioning
confidence: 99%
“…In the studied literature there is a diversity of articles that use bibliometric techniques to analyze scientific productions, without being restricted to a specific area, according to the works developed by Kozak, Bornman, and Leydesdorff [2014], which dealt with how research was affected by the demise of the Soviet Union; Romanelli et al [2018], who presented analyzes on ecological restoration; and Sweileh [2018], who dealt with the use of drugs related to HIV (human immunodeficiency virus). Bibliometric techniques are known to be used to analyze scientific branches, but these analyzes are not considered infallible [WANG et al, 2014;KHALIL;GOTWAY CRAWFORD, 2015]. The lack of perception by databases in the case of the same words and acronyms, that is, the same words with only different spellings, is one of the limitations of bibliometrics that must be circumvented by careful analysis of the data collected in search of synonyms.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of perception by databases in the case of the same words and acronyms, that is, the same words with only different spellings, is one of the limitations of bibliometrics that must be circumvented by careful analysis of the data collected in search of synonyms. Another problem linked to the indicators used in bibliometric studies refers to the fact that the analysis of these indicators is quantitative, so they do not provide a qualitative analysis of the contributions of each work to the literature [KHALIL;GOTWAY CRAWFORD, 2015;OKUBO, 1997]. In this context, the objective of the present study was to evaluate the use of the Delphi method in scientific articles with authors with affiliations in Brazilian institutions.…”
Section: Introductionmentioning
confidence: 99%
“…This list is not intended to be comprehensive. Khalil and Crawford [15] identified 1,387 articles using BRFSS data from 1984 through 2012, and noted that in the last 10 years, publications focused on national data were most frequent.…”
Section: Introductionmentioning
confidence: 99%